Exploring the impact of living with dyslexia: The perspectives of children and their parents. (4th May 2017) - Leitão, Suze; Dzidic, Peta; Claessen, Mary; Gordon, Joanne; Howard, Kate; Nayton, Mandy; Boyes, Mark E.
Abstract: Purpose : A small but growing body of literature indicates that children with dyslexia are at elevated risk of internalising and externalising mental health problems. However, little research addresses why this might be the case, particularly from the point of view of the children or their parents. This study therefore aimed to explore the lived experiences of children with dyslexia, and their parents. Method : Drawing on a phenomenological approach, 13 children with dyslexia and 21 parents were interviewed. The semi-structured interviews were analysed thematically. Result : Dyslexia was seen to impact at the individual, family and community level. Children's accounts of their experiences were ecologically situated at both the micro and mesosystem levels of Bronfenbrenner's ecological model, while parent's accounts extended to include the exosystem. Both also reflected on "difference", a theme related to cultural and attitudinal views at the level of the macrosystem. Conclusion : Presentation of the themes contrasts the experiences of children and parents, illustrating that the experience of dyslexia is indicative of broader challenges associated with societal values and attitudes that privilege perceived ability and shame difference. This study provides information that could be used to inform and educate families and teachers about the impact of living with dyslexia.